Comparative Quality Evaluation of Different Brands of ‘Triphala’: A Polyherbal Medicine in Sri Lanka - Ramitha, P.; Thuvaragan, S.; Vinotha, S.; Srikaran, R.; Nahmagal, K. (J Young Pharm, 2021; 13(3) : 226-229, 2021)
Background: Triphala is a well-known polyherbal formulation widely used as an herbal, complementary and alternative medicine for various ailments, especially for gastrointestinal problems, and it is used as a dietary supplement for long years. Objectives: Objective of this study was to comparatively evaluate the quality of three marketed brands of Triphala tablets (Brand T1 and T2 ) and capsules (Brand T3 ) which are available in Sri Lanka. Materials and Methods: This laboratory based experimental qualitative study was done among three brands of Triphala. Phytochemical screening was carried out for all those brands. Physicochemical tests were also performed to determine pH, moisture content, and loss on ignition, ash values and extractive values. Data were analysed by using Statistical Package of Social Sciences 23. Results: Physicochemical tests revealed that all three brands failed to comply with pharmacopoeial limits at least in one physicochemical test. According to ANOVA test, there was significant difference between results of physicochemical tests of marketed brands of Triphala. Conclusion: All three Triphala brands did not meet the quality standards. Quality of herbal medicine marketed in Sri Lanka should be monitored and regularized by relevant authorities.
Keywords: Marketed Brands; Phytochemicals Test; Phytochemical Screening; Quality; Srilanka; Triphala